Neural correlates of evoked phantom limb sensations - Andoh, Jamila; Kleinböhl, Dieter; Flor, Herta (Biological psychology, 2017)
Previous work showed the existence of changes in the topographic organization within the somatosensory cortex (SI) in amputees with phantom limb pain, however, the link between nonpainful phantom sensations such as cramping or tingling or the percept of the limb and cortical changes is less clear. We used functional magnetic resonance imaging (fMRI) in a highly selective group of limb amputees who experienced inducible and reproducible nonpainful phantom sensations. A standardized procedure was used to locate body sites eliciting phantom sensations in each amputee. Selected body sites that could systematically evoke phantom sensations were stimulated using electrical pulses in order to induce phasic phantom sensations. Homologous body parts were also stimulated in a group of matched controls. Activations related to evoked phantom sensations were found bilaterally in SI and the intraparietal sulci (IPS), which significantly correlated with the intensity of evoked phantom sensations. In addition, we found differences in intra- and interhemispheric interaction between amputees and controls during evoked phantom sensations. We assume that phantom sensations might be associated with a functional decoupling between bilateral SI and IPS, possibly resulting from transcallosal reorganization mechanisms following amputation.
Gesehen am 24.04.2018